Transcultural communication - Hepp, Andreas (John Wiley & Sons Ltd, 2015)
"Provides an accessible and engaging introduction to the exciting possibilities and inevitable challenges presented by the proliferation of transcultural communication in our mediatized world"--Provided by publisher.